1996
DOI: 10.1111/j.1528-1157.1996.tb00571.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Indicators of Genetic Susceptibility to Epilepsy

Abstract: We evaluated clinical indicators of genetic susceptibility to epilepsy in the families of 1,957 adults with epilepsy (probands) ascertained from voluntary organizations. Very few of the probands in this series had idiopathic epilepsy syndromes. Among relatives of probands with postnatal CNS insults, risks of epilepsy were no higher than in the general population. Risk was increased in relatives of probands without identified CNS insults (i.e., those with idiopathic/cryptogenic epilepsy) or with neurological de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
51
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 26 publications
(15 reference statements)
1
51
0
3
Order By: Relevance
“…In addition, risk was significantly increased for epilepsy associated with neurodeficits among relatives of probands with idiopathic/cryptogenic epilepsy (2.1-fold, see Table 2). The consistency of these findings provides support for the possibility of a shared genetic susceptibility to epilepsy and cerebral palsy, as we and others have suggested [8,[19][20][21].Risk of epilepsy was not increased among relatives of probands with postnatal symptomatic epilepsy. Schaumann and associates [22] also reported that risk was not increased in relatives of probands with post-traumatic epilepsy.…”
supporting
confidence: 62%
See 3 more Smart Citations
“…In addition, risk was significantly increased for epilepsy associated with neurodeficits among relatives of probands with idiopathic/cryptogenic epilepsy (2.1-fold, see Table 2). The consistency of these findings provides support for the possibility of a shared genetic susceptibility to epilepsy and cerebral palsy, as we and others have suggested [8,[19][20][21].Risk of epilepsy was not increased among relatives of probands with postnatal symptomatic epilepsy. Schaumann and associates [22] also reported that risk was not increased in relatives of probands with post-traumatic epilepsy.…”
supporting
confidence: 62%
“…In this study, we extended our previous investigations of epilepsy in the families of probands from the EFSCU [8,17], by evaluating the relations between genetic and environmental factors in their effects on risk. For this purpose, we computed SMRs for specific etiologies of epilepsy in the relatives of probands with specific etiologies, using age-and decade-specific incidence of epilepsy from the Rochester-Olmsted County Record Linkage Project as the reference.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A influência de fatores genéticos nas epilepsias sempre foi suspeitada, sendo que a recorrência familiar foi inicialmente demostrada nas epilepsias generalizadas [1][2][3][4][5] e mais recentemente também nas epilepsias parciais [6][7][8][9][10][11] . Clinicamente, muitas destas síndromes se apresentam de forma heterogênea, o que pode dificultar o reconhecimento da recorrência familiar.…”
unclassified